Impact of team role distribution on performance in civil engineering education: A TREO survey analysis - García-Ramírez, Yasmany (Edelweiss Applied Science and Technology, 2025)
Effective teamwork is essential in civil engineering education, as it mirrors the interdisciplinary collaboration required in professional practice. However, determining the optimal team composition strategy remains challenging due to students’ diverse skills and experience levels. This study examines the impact of different role distribution strategies using the Teamwork Reflection and Evaluation Overview (TREO) survey among civil engineering students. Two groups were formed: Group A, with balanced roles (±0.5 deviation from the group average), and Group B, with imbalanced roles. A total of 101 students participated, with 46 from Group A and 44 from Group B responding to the survey. No significant differences in academic performance were found (t = -0.81, p = 0.418); however, Group A reported higher satisfaction with leadership roles (87%) and a more structured project management approach. The study revealed a predominance of the Doer role, while the Organizer and Connector roles had lower representation. Key challenges included communication, task distribution, and individual commitment. Although role distribution did not directly impact grades, the findings underscore the need for structured team-building interventions to enhance collaboration, accountability, and role effectiveness in engineering education.